2020
DOI: 10.1016/j.isci.2020.101051
|View full text |Cite
|
Sign up to set email alerts
|

Selective C−C Coupling by Spatially Confined Dimeric Metal Centers

Abstract: Direct conversion of carbon dioxide (CO2) to high-energy fuels and high-value chemicals is a fascinating sustainable strategy. For most of the current electrocatalysts for CO2 reduction, however, multi-carbon products are inhibited by large overpotentials and low selectivity. For practical applications, there remains a big gap of knowledge in proper manipulation of the C−C coupling process. Herein, we exploit dispersed 3d transition metal dimers as spatially confined dual reaction centers for selective reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…However, owing to the complexity of the CO 2 RR mechanism and the multifarious reaction products, more experimental and theoretical studies are required. TM 2 @phthalocyanine Mn 2 @phthalocyanine CH 3 OH −0.84 2017 [123] TM 2 @C 2 N Cu 2 @C 2 N CH 4 /C 2 H 4 −0.23 (CH 4 )/−0.76 (C 2 H 4 ) 2018 [124] Ni 2 , Co 2 , NiCo@C 2 N NiCo@C 2 N CH 4 −0.23 2019 [125] TM 1 /TM 2 @C 2 N CuCr/CuMn@C 2 N CH 4 −0.37/−0.32 2020 [50] TM 1 /TM 2 @N 6 -C CuMn, NiMn, NiFe@N 6 -C CO ≈−0.43 (CuMn); ≈−0.45 (NiFe); ≈−0.65 (NiMn) 2020 [52c] Fe 2 @holey N-doped carbon monolayers Fe 2 @C 2 N C 2 H 5 OH −0.70 2020 [126] Fen@graphdiyne (n = 1-4) Fe 2 @graphdiyne CH 4 −0.29 2020 [127] www.afm-journal.de www.advancedsciencenews.com…”
Section: (19 Of 25)mentioning
confidence: 99%
“…However, owing to the complexity of the CO 2 RR mechanism and the multifarious reaction products, more experimental and theoretical studies are required. TM 2 @phthalocyanine Mn 2 @phthalocyanine CH 3 OH −0.84 2017 [123] TM 2 @C 2 N Cu 2 @C 2 N CH 4 /C 2 H 4 −0.23 (CH 4 )/−0.76 (C 2 H 4 ) 2018 [124] Ni 2 , Co 2 , NiCo@C 2 N NiCo@C 2 N CH 4 −0.23 2019 [125] TM 1 /TM 2 @C 2 N CuCr/CuMn@C 2 N CH 4 −0.37/−0.32 2020 [50] TM 1 /TM 2 @N 6 -C CuMn, NiMn, NiFe@N 6 -C CO ≈−0.43 (CuMn); ≈−0.45 (NiFe); ≈−0.65 (NiMn) 2020 [52c] Fe 2 @holey N-doped carbon monolayers Fe 2 @C 2 N C 2 H 5 OH −0.70 2020 [126] Fen@graphdiyne (n = 1-4) Fe 2 @graphdiyne CH 4 −0.29 2020 [127] www.afm-journal.de www.advancedsciencenews.com…”
Section: (19 Of 25)mentioning
confidence: 99%
“…[ 52 ] The first‐principles calculations showed that the limiting two adjacent metal atoms in the vacancy of the carrier to form a synergetic active center can not only fix two CO 2 molecules at the same time, but also spatially limit the reaction path that is conducive to C–C coupling to form C2 or C2+ high‐valued chemical products. [ 159 ] Analogously, the synergistic effects by interactions of adjacent sites also apply to the before‐mentioned ultrahigh‐density SACs, [ 30,84 ] where their synergistic sites are highly dense and omnidirectional on support, thus leading to better catalytic properties in heterogeneous catalysis.…”
Section: Heterogeneous Catalysis Applications Of Afcsmentioning
confidence: 99%
“…The electron accumulation and depletion regions are represented in different colors in Figure c. The charge transfer to CO 2 from the MBene surface and the electron transfer from transition metal to boron further contribute to the stability of the adsorption configurations. , For the M 3 B 4 -type MBene substrate, the favorable adsorption site is on top of the metal atom with adsorption energies of −0.06 eV, −0.25 eV, and −0.05 eV, corresponding to Nb 3 B 4 , Ta 3 B 4 , and V 3 B 4 , respectively. Furthermore, for Hf 2 B 2 and Zr 2 B 2 , the sites of boron also provide an energetically preferred adsorption energy for CO 2 reduction.…”
Section: Computational Methodsmentioning
confidence: 99%